Urban vegetation dynamics and thermal responses to the COVID-19 pandemic mobility restrictions in Yogyakarta - Mahardiani, Insan Wastuwidya (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2026)
Changes in human activity during the COVID-19 pandemic affected urban environmental conditions, particularly vegetation density and land surface temperature. This study analyzes vegetation and surface temperature changes in Yogyakarta City using Landsat-8 imagery from 2017 to 2022. A remote sensing approach was applied to derive vegetation indices and surface temperature and to compare pre-pandemic and pandemic periods. The results show an increase in minimum vegetation values from 0.027 to 0.048, while mean and maximum values decreased from 0.118 to 0.108 and from 0.309 to 0.276. Vegetation demonstrated a strong negative relationship with built-up areas, with correlation coefficients of −0.780 before the pandemic and −0.721 during the pandemic. Land surface temperature showed an overall cooling trend. These findings confirm that reduced human activity influenced urban thermal dynamics and vegetation patterns, emphasizing their importance for urban environmental resilience.